A disimprisoned epic : form and vision in Carlyle's French Revolution - Cumming, Mark. (Philadelphia : University of Pennsylvania Press, 1988)
In A Disimprisoned Epic, Mark Cumming elucidates the formal genesis of the French Revolution in Carlyle's literary criticism and reestablishes it as an epic experiment in literary form.
Frontmatter -- Contents -- Abbreviations -- Preface -- One: Carlyle Reading -- Two: The Critic as Copernicus -- Three: Experiments in Genre -- Four: History and Epic -- Five: New and Antiquated Myths -- Six: Satire, Elegy, and Farce-Tragedy -- Seven: Emblems and Fragments -- Eight: Allegory and Phantasmagory -- Nine: The Liberation of Epic -- Notes -- Index
Includes bibliographical references (pages 167-184) and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
In English.
Keywords: Carlyle, Thomas, -- 1795-1881 -- Knowledge -- History; Carlyle, Thomas, -- 1795-1881.; Carlyle, Thomas, -- 1795-1881 -- Et l'Histoire.; Carlyle, Thomas, -- 1795-1881; Carlyle, Thomas, -- 1795-1881; French revolution (Carlyle, Thomas); France -- History -- Revolution, 1789-1799 -- Historiography; Epic literature, English -- History and criticism; History in literature; Littérature épique anglaise -- Histoire et critique; Histoire de la littérature.; France -- Histoire -- 1789-1799 (Révolution) -- Historiographie; Histoire dans la littérature.; LITERARY COLLECTIONS -- Essays; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; History; Epic literature, English; Historiography; History in literature; France; 1789-1799; Criticism, interpretation, etc; History